Transgene Biocontainment Strategies for Molecular Farming - Michael Clark; Maciej Maselko; Maciej Maselko; Maciej Maselko (Frontiers in Plant Science, 2020)
Advances in plant synthetic biology promise to introduce novel agricultural products in the near future. ‘Molecular farms’ will include crops engineered to produce medications, vaccines, biofuels, industrial enzymes, and other high value compounds. These crops have the potential to reduce costs while dramatically increasing scales of synthesis and provide new economic opportunities to farmers. Current transgenic crops may be considered safe given their long-standing use, however, some applications of molecular farming may pose risks to human health and the environment. Unwanted gene flow from engineered crops could potentially contaminate the food supply, and affect wildlife. There is also potential for unwanted gene flow into engineered crops which may alter their ability to produce compounds of interest. Here, we briefly discuss the applications of molecular farming and explore the various genetic and physical methods that can be used for transgene biocontainment. As yet, no technology can be applied to all crop species, such that a combination of approaches may be necessary. Effective biocontainment is needed to enable large scale molecular farming.